Pengaruh Trust, Corporate Image dan Pemanfaatan Fintech terhadap Keputusan Muzakki dalam Membayar Zakat di Dompet Dhuafa Sulsel degan Religiusitas sebagai Variabel Moderasi - Islamyanti, Nur; Yunus, Ayu Ruqayyah; Katman, Muhammad Nasri (ISLAMIKA, 2024)
The aim of this research is to examine the extent to which trust, corporate image and the use of fintech have an impact on muzakki's decision to pay zakat in Dompet Dhuafa, South Sulawesi. This research uses a quantitative descriptive research design. This research relies on primary and secondary data sources. Data received directly from the research location with muzakki respondents is referred to as primary data. In this research, questionnaires, interviews and documentation were used to collect data. The SmartPLS 4.0 data processing application is used in research data analysis. Based on the regression results, the variables Trust (X1), corporate image (x2), and use of fintech (x3) have a positive and large influence on the muzakki's decision variable in paying zakat (Y). Furthermore, the Religiosity variable (Z) can moderate (strengthen) the influence of trust on the muzakki's decision to pay zakat, but cannot moderate (weaken) the influence of corporate image on the muzakki's decision to pay zakat, and cannot moderate (weaken) the influence of fintech. on the muzaki's decision to pay zakat.